The political in contemporaneity: Approaches from the psychopolitics of Byung-Chul Han. - Ullauri Betancourt, Santiago Andrés; Rivas Plata, Anthony Medina; Cáceres Silva, Andrea Vanessa (Universidad Hemisferios, 2024)
The notion of the political in the contemporary era has developed a new paradigm characterized by structured individualism under psychic control and self-exploitation. In this context, Byung-Chul Han argues that, under the neoliberal system, power no longer operates through physical discipline or external coercion, but through psychological manipulation. The individual is transformed into an